Preventing Chronic Obstructive Pulmonary Disease (COPD)The Role of Electric Smoking Alternatives: A Literature Review - Nurul Imam; Taufan Citra Darmawan; Khalifatus Zuhriyah Alfianti (PT Nuansa Fajar Cemerlang, 2025)
Introduction: The incidence rate of Chronic Obstructive Pulmonary Disease (COPD) remains high, especially in developing countries, with cigarette consumption being a major risk factor contributing to the prevalence of the disease. The purpose of this article review is to explain the role of e-cigarette alternatives in preventing COPD Method: A literature search was conducted in February 2025. The strategy used to search for articles is to use the PICOS framework. The article was identified with the keywords